ScienceVR: a virtual reality framework for STEM education, simulation and assessment - Qorbani, Sam; Arya, Ali; Nowlan, Nuket; Abdinejad, Maryam (My University, 2021)
This paper addresses the use of Virtual Reality (VR) in Science, Technology, Engineering, and Math (STEM) education. There are limited studies investigating the proper design and effectiveness of VR in STEM education, and current VR frameworks and applications lack explicit links to the established learning theories and assessment mechanisms to evaluate learning outcomes. We present ScienceVR, an educational virtual reality design framework, illustrated through a science laboratory prototype, to bridge some of the gaps identified in the design and development of a VR environment for learning. We established design guidelines and implemented an in-app data collection system to measure users’ learning, performance, and task completion rate. Our evaluation using ANOVA and other non-parametric methods with 36 participants in three groups: immersive VR (IVR), desktop VR(DVR), and 2D indicated improved usability and learning outcomes for the IVR group. Task completion rate in the IVR group was higher (68% compared to DVR with 50%). For memorability, the IVR condition performed better than DVR while for learnability, IVR&DVR performed significantly better than 2D. IVR group has performed better and faster with more accuracy compared to the DVR group in completing the tasks.
Presented November 15-17, 2021, at the IEEE International Conference on Artificial Intelligence and Virtual Reality (AIVR) held virtually.
Keywords: virtual reality; STEM education; immersion; simulation; education and technology